Causative morphology of Japanese and Indonesian language - Br Barus, Murniati (Abdul Media Literasi, 2025)
The research aims to describe the forms of causative verbs and their markers in the Japanese and Indonesian languages; causative sentences and their meanings in the Japanese and Indonesian languages, as well as the similarities and differences of causative constructions in the Japanese and Indonesian languages. The research applies structural linguistics, semantics, and contrastive analysis to compare causative verbs, causative constructions, and causative meanings in Japanese and Indonesian languages. The research findings show that the forms of causative verbs in the Japanese language can be divided into two types: morphological causative and lexical causative. Meanwhile, Indonesian causative verbs are categorised into three types: analytic causative, morphological causative, and lexical causative. The causative sentence constructions in Japanese and Indonesian are derived from non-causative sentences by changing the predicate into a causative verb. The Japanese morphological causative construction can be divided into three patterns: subject ga direct object ni V-aseru/V-saseru and subject ga direct object o V-aseru/V-saseru for intransitive bases, as well as subject ga nondirect object ni direct object o V-aseru/V-saseru for transitive bases—lexical causative construction in Japanese, subject ga direct object o causative verb. Unlike the Japanese language, the causative sentence constructions in Indonesian take three types: analytic causative pattern, morphological causative, and lexical patterns.